Manufacturing viral gene therapy vectors: general approaches and challenges - Gray, John T. (Henry Stewart Talks, 2014)
Manufacturing of Viral Gene Therapy Vectors, Different types of vector production systems, Concepts for the design of viral vector production cells, Specific viral vector production systems for adenovirus, adeno-associated virus, gamma-retrovirus, and lentivirus, Downstream processing, Regulatory considerations